A comparative study for accuracy assessment of PPP technique using GPS and GLONASS in urban areas. (June 2015) - Alkan, Reha Metin; İlçi, Veli and Ozulu, İ. Murat and Saka, M. Halis
Highlights: The usability of PPP in urban areas with GPS-only and GPS + GLONASS is investigated. We use CSRS-PPP and magicGNSS /PPP on-line processing service. Increase in the number of satellites is vital especially in urban areas. Abstract: In recent years, the usage of the Precise Point Positioning (PPP) has increased due to its ease of use, providing high accuracy as well as reducing the field operational costs by using only a single GNSS receiver. Moreover, it does not require any additional reference station data or CORS-like network data. It is a positioning technique that has been extensively investigated and used in a variety of applications, mainly for conventional surveying applications and time-transfer, ionospheric and tropospheric characterization. In GNSS positioning, limited satellite visibility in obstructed areas and poor satellite geometry adversely affect the accuracy of results. With the revitalization of the GLONASS system reaching to full global coverage, PPP studies have focused on combined GPS and GLONASS solutions. The goal of this study is to investigate the usability of PPP technique in urban areas with GPS-only and GPS + GLONASS data by the use of online-PPP services for sub-decimeter surveying applications. For this purpose, test measurements were conducted in Çorum province of Turkey. Collected data were evaluated with two commonly used PPP services, namely CSRS-PPP operated by the Geodetic Survey Division of Natural Resources Canada (NRCan) and magicGNSS /PPP developed by Spanish GMV Aerospace and Defense Co. Results obtained from this study revealed that for some cases, the use of GLONASS with GPS raises the number of satellites used in the solution twice as much as compared to GPS-only. However, unless satellites geometry gets better, the use of GLONASS has no significant role in strengthening the accuracy of results. The results indicate that an increase in the number of satellites is vital especially in urban areas where minimum number of satellites for a solution may not be obtained. Also, it was observed that when the sufficient numbers of GPS satellites with good geometry are available combining GPS together with GLONASS may not bring any significant contribution to the solution.